High-performance porous magnetic copper sulfide thermoelectric material and preparation method thereof
By adding Fe3O4 to copper sulfide to form a porous structure and introducing Fe elements, the problem of poor performance of copper sulfide thermoelectric materials is solved, the Seebeck coefficient and stability are improved, the thermoelectric superiority is significantly improved, and the high-performance porous magnetic properties are achieved Preparation of copper sulfide thermoelectric materials.
Patent Information
- Application Number
- CN202411301555.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The performance of existing copper sulfide thermoelectric materials is poor, the Seebeck coefficient is low, the thermal conductivity is high, and the migration of Cu ions under the action of the external field leads to poor stability, affecting the thermoelectric performance.
The oxide Fe3O4 is added to copper sulfide to form a porous structure, reduce thermal conductivity, and introduce Fe elements to improve Seebeck coefficient and stability. High-performance porous magnetic copper sulfide thermoelectric materials are prepared through mechanical alloying and discharge plasma sintering processes.
The Seebeck coefficient and stability of copper sulfide material are improved, the thermal conductivity is reduced, the thermoelectric superiority is significantly improved, and the thermoelectric properties and mechanical strength of the material are enhanced.
Smart Images

Figure CN119160928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous magnetic thermoelectric materials, and in particular to a high-performance porous magnetic copper sulfide thermoelectric material and a preparation method thereof. Background Art
[0002] As energy issues become increasingly serious, how to balance the relationship between "energy", "environment" and "development" is the common goal of cross-disciplinary and coordinated development in many fields. As a new type of green energy conversion material, thermoelectric materials can not only directly convert any form of thermal energy into electrical energy, but also use the temperature difference generated after power is turned on to manufacture precise temperature control or refrigeration devices. Among them, electrical energy can be directly converted into thermal energy for use in the field of electrothermal temperature difference, that is, cooling or heating, such as chip refrigeration, 5G component refrigeration, laser component refrigeration, thermoelectric refrigerators, drug refrigeration and other civil, biological, and medical fields; it can also be converted into electrical energy through waste heat recovery to complete the energy conversion of temperature difference to electricity, such as industrial waste / waste heat recovery, automobile exhaust waste heat power generation, and even human body temperature conversion, artificial satellites, deep space probes and other civil, aerospace, military and other fields.
[0003] Thermoelectric conversion efficiency is measured by the dimensionless thermoelectric figure of merit ZT, which can be obtained by the following formula: ZT = S 2 σT / κ, where S, σ, T, and κ represent the Seebeck coefficient, electrical conductivity, absolute temperature, and thermal conductivity of the material, respectively. Among them, the three important performance parameters S, σ, and κ show a mutually restrictive and coupled relationship with the change of carrier concentration. How to achieve the coordinated optimization of these parameters by adjusting the carrier concentration is the core of maintaining the high thermoelectric performance of the material. Currently, high-performance thermoelectric materials include Bi2Te3, PbTe, PbS, GeTe alloys, etc., but these materials are expensive, have small raw material reserves, and are highly toxic. Therefore, it is also an important research task to find and study compounds composed of non-toxic, harmless, cheap, abundant, and industrially applicable elements as suitable thermoelectric materials.
[0004] Cu1.8S material is a kind of intrinsic p-type semiconductor material, which has the advantages of high element abundance, low raw material cost, and green and pollution-free. 1.8 S has a rhombohedral phase structure (R-3m) at room temperature and transforms into a cubic phase structure (Fm-3m) when the temperature rises above 361K. This material is a superionic conductor, that is, Cu ions migrate in the lattice framework of S with extremely high mobility. 1.8 S materials have high electrical conductivity. But it has always been a barrier for Cu 1.8 The commercial application of S material is due to its low Seebeck coefficient and high thermal conductivity. In addition, Cu ions will move in Cu under the action of external field (temperature field / electric field). 1.8Directional migration occurs inside the S material, and Cu single substance is precipitated at the cathode. This will seriously affect the thermoelectric performance of the material, cause the contact resistance to increase, and affect the use of the device. Based on this, researchers have conducted a lot of research on the problems of poor thermoelectric performance and insufficient stability. Zhang Boping et al. used single substance Cu powder, S powder, and doped element A powder as raw materials, and used mechanical alloying reaction combined with room temperature high pressure sintering technology to obtain nanocrystalline Cu-S based bulk thermoelectric materials with fine grains and dense structure (CN110117191A), but the copper sulfide material prepared by this method has poor electrical properties due to the small grain size, and the thermoelectric performance has not been effectively improved. Qiu Pengfei et al. distributed at least one ion barrier layer between any two adjacent fast ion conductor thermoelectric materials in the thermoelectric arm connected by n segments of fast ion conductor thermoelectric materials along the direction of the external field to improve the service stability of fast ion conductor thermoelectric materials (CN 110544741A), but this method is difficult to be applied to mass production, and multiple ion barriers may reduce the mechanical strength of the entire thermoelectric device. Therefore, it is of great significance to develop a porous magnetic copper sulfide thermoelectric material with excellent thermoelectric properties and its preparation process. Summary of the invention
[0005] The present invention aims to provide a high-performance porous magnetic copper sulfide thermoelectric material and a preparation method thereof, so as to solve the problem of poor performance of existing copper sulfide thermoelectric materials.
[0006] To achieve the above object, the present invention adopts the following technical solution: a high-performance porous magnetic copper sulfide thermoelectric material, comprising a matrix phase Cu 1.8 S and the second phase Fe3O4, whose general chemical formula is Cu 1.8 Sx%Fe3O4, where 0.5≤x≤20.
[0007] The principles and advantages of this solution are: in this technical solution, in view of the poor performance of existing copper sulfide thermoelectric materials in the prior art, this technical solution comprehensively optimizes copper sulfide thermoelectric materials and preparation processes: by adding oxides to copper sulfide, the pore-forming effect is achieved, and the porous structure ensures the low thermal conductivity of the material, solving the problem of high thermal conductivity of intrinsic copper sulfide; in addition, while ensuring the porous structure, the added oxides of this technical solution achieve the doping of Fe elements in the matrix, introduce a second phase containing iron elements, and technically achieve the magnetic transformation of copper sulfide, improve the Seebeck coefficient of the material, and solve the problem of low Seebeck coefficient of intrinsic copper sulfide; not only that, by introducing the second phase containing iron elements, the thermal conductivity of the material can be further reduced, and the Fe element inhibits the migration of Cu ions, solving the problem of poor intrinsic stability of copper sulfide materials, with outstanding advantages.
[0008] In summary, the beneficial effects of this technical solution are:
[0009] 1. In this technical solution, the addition of Fe3O4 produces SO2, which generates pores in the copper sulfide matrix, forming a porous copper sulfide thermoelectric material. The copper-rich phase in the matrix increases, which can reduce the thermal conductivity of the material;
[0010] 2. In this technical solution, the introduction of magnetic iron oxide (Fe3O4) causes the antimagnetic copper sulfide material to undergo magnetic conversion, becoming a porous copper sulfide thermoelectric material with magnetic properties, effectively improving the Seebeck coefficient of the copper sulfide material;
[0011] 3. The Fe3O4 in this technical solution is 1.8 Fe doping is achieved in the S matrix to form a second phase containing iron elements. By optimizing the carrier concentration, the thermal conductivity of the material is effectively reduced. At the same time, the Fe element can inhibit the long-range migration of Cu ions in the group, thereby improving the stability of the copper sulfide material.
[0012] 4. In this technical solution, the dispersed distribution in Cu 1.8 The Fe3O4 in the S matrix material introduces additional phase interfaces, which helps to enhance the Cu 1.8 The phonon scattering effect in S thermoelectric materials significantly reduces the lattice thermal conductivity of the material, which is beneficial to improving the thermoelectric figure of merit of the material.
[0013] Preferably, as an improvement, Fe3O4 is a magnetic black oxide powder, and the added amount of Fe3O4 is 0.5-20wt%.
[0014] In this technical solution, the oxide powder is added to copper sulfide to cause the volatilization of sulfur elements, and the generated SO2 plays a good role in forming pores in the matrix. Moreover, due to its magnetic properties, it can make the copper sulfide thermoelectric material complete the magnetic transformation, improve the Seebeck coefficient, and inhibit the Cu 1.8 The long-range migration of Cu ions in S materials can improve the stability of the materials. During the technical research and development stage, the inventors found that the Fe3O4 content has a key influence on the thermal conductivity of thermoelectric materials. Too little Fe3O4 content is difficult to block the migration of Cu ions, and excessive Fe3O4 will greatly increase the thermal conductivity of copper sulfide thermoelectric materials.
[0015] Preferably, as an improvement, a method for preparing a high-performance porous magnetic copper sulfide thermoelectric material comprises the following steps:
[0016] Step (1) Cu 1.8 Preparation of Sx% Fe3O4 precursor powder: Cu single substance powder, S single substance powder and Fe3O4 magnetic powder are placed in a ball mill for mechanical alloying to obtain Cu 1.8 Sx%Fe3O4 precursor powder;
[0017] Step (2) Cu 1.8 Sintering of Sx%Fe3O4 bulk: Sinter the Cu prepared in step (1) 1.8 The Sx%Fe3O4 precursor powder is sintered by spark plasma sintering to obtain a porous magnetic copper sulfide thermoelectric material.
[0018] Preferably, as an improvement, in step (1), the mechanical alloying process is carried out under a protective atmosphere.
[0019] Preferably, as an improvement, the protective atmosphere is 5% H2+95% Ar.
[0020] Preferably, as an improvement, in step (1), the purity of the Cu single substance powder and the S single substance powder are both greater than 99.99%.
[0021] Preferably, as an improvement, in step (1), the weight ratio of the balls to the material during ball milling is 20 to 50:1, the rotation speed during ball milling is 300 to 600 rpm, and the ball milling time is 1 to 4 hours.
[0022] Preferably, as an improvement, in step (2), the sintering temperature is 300-500° C., the sintering time is 5-30 min, and the sintering pressure is 10-50 MPa.
[0023] Preferably, as an improvement, in step (2), the sintering temperature is 500° C., the sintering time is 5 min, and the sintering pressure is 50 MPa.
[0024] In this technical solution, in addition to optimizing the thermoelectric materials, the performance of the raw materials and the preparation process are also improved in an integrated manner: First, in terms of material performance, high-purity Cu single-element powder and S single-element powder can reduce the amount of impurities produced, thereby avoiding the poor thermoelectric performance of the prepared thermoelectric composite materials. In terms of optimization of the preparation process: During the mechanical alloying stage, the mechanical alloying reaction is carried out in an environment with a protective atmosphere of 5% H2 + 95% Ar, which can effectively prevent the raw materials from being oxidized and contaminated. The use of unidirectional operation is conducive to the full diffusion of elements, making the reaction more complete. In the sintering stage, the prepared Cu is optimized through the integrated optimization of the sintering temperature, time and pressure. 1.8 S copper sulfide thermoelectric material has high density, good thermoelectric performance, and is not easy to explode during sintering.
[0025] In summary, the beneficial effects of this technical solution are:
[0026] 1. In this technical solution, during the ball milling synthesis of Cu 1.8When the precursor powder is Sx%, the ball milling time and the ball milling speed are adjusted to make the Cu element, S element and Fe3O4 react completely, and the second phase of Fe3O4 can be distributed more evenly in the Cu 1.8 S matrix material, to ensure the stability of the thermoelectric performance of the thermoelectric material;
[0027] 2. In this technical solution, by 1.8 The Sx%Fe3O4 precursor powder is subjected to spark plasma sintering to rapidly form a bulk porous magnetic copper sulfide thermoelectric material, ensuring that the thermoelectric material meets practical use.
[0028] 3. This technical solution, through magnetic measurement, proves that the Fe3O4 second phase can convert non-magnetic Cu 1.8 S thermoelectric material is converted into a magnetic thermoelectric material; by characterizing the phase structure, micromorphology and thermoelectric properties of the prepared porous magnetic copper sulfide thermoelectric material, it is found that the copper sulfide thermoelectric material contains a Cu1.8S matrix phase and a Fe3O4 second phase, which can significantly improve its stability while improving its thermoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The morphology of Example 1 of the present invention and Comparative Example 1;
[0030] Figure 2 It is the XRD comparison diagram of Example 1 of the present invention and Comparative Example 1;
[0031] Figure 3 is a curve diagram showing the change of conductivity with temperature in Example 1 of the present invention and Comparative Example 1;
[0032] Figure 4 is a curve diagram showing the Seebeck coefficient of Example 1 of the present invention and Comparative Example 1 changing with temperature;
[0033] Figure 5 is a curve diagram showing the change of thermal conductivity with temperature in Example 1 of the present invention and Comparative Example 1;
[0034] Figure 6 It is a curve diagram showing the thermoelectric figure of merit (ZT value) of Example 1 of the present invention and Comparative Example 1 changing with temperature;
[0035] Figure 7 It is the magnetization curve diagram of the samples of Example 1 of the present invention and Comparative Example 1 at a temperature of 323K. DETAILED DESCRIPTION
[0036] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.
[0037] Program Overview:
[0038] A high-performance porous magnetic copper sulfide thermoelectric material, comprising a matrix phase Cu 1.8 S and the second phase Fe3O4, whose general chemical formula is Cu 1.8 Sx%Fe3O4, wherein 0.5≤x≤20, Fe3O4 is a black oxide powder with magnetic properties.
[0039] A method for preparing a high-performance porous magnetic copper sulfide thermoelectric material comprises the following steps:
[0040] Step (1) Cu 1.8 Preparation of Sx% Fe3O4 precursor powder: Cu single substance powder, S single substance powder and Fe3O4 magnetic powder are placed in a planetary ball mill and mechanically alloyed under a protective atmosphere to obtain Cu 1.8 Sx% Fe3O4 precursor powder; the purity of Cu elemental powder and S elemental powder is greater than 99.99%; the addition amount of Fe3O4 is 0.5-20wt%; the weight ratio of ball and material during ball milling is 20-50:1, the rotation speed during ball milling is 300-600rpm, and the ball milling time is 1-4h; the protective atmosphere is 5% H2+95% Ar;
[0041] Step (2) Cu 1.8 Sintering of Sx%Fe3O4 bulk: Sinter the Cu prepared in step (1) 1.8 The Sx%Fe3O4 precursor powder is sintered by spark plasma sintering, the sintering temperature is 300-500°C, the sintering time is 5-30min, and the sintering pressure is 10-50Mpa to obtain a porous magnetic copper sulfide thermoelectric material.
[0042] Embodiment: In order to further illustrate the advantages of the present technical solution, the following 7 embodiments and 5 comparative examples are designed. The difference between the embodiments lies in the selection of magnetic powder, the addition amount, the addition amount of raw materials and the mass percentage of the second phase, and the difference between the comparative examples lies in the selection of oxide types. See Table 1 for details:
[0043] Table 1
[0044]
[0045]
[0046] Taking Example 1 as an example, a method of obtaining a porous magnetic copper sulfide thermoelectric material with excellent thermoelectric properties by using iron oxide according to the present invention is described in detail:
[0047] A method for preparing a high-performance porous magnetic copper sulfide thermoelectric material comprises the following steps:
[0048] Step (1) Cu 1.8 S-2%Fe3O4 precursor powder preparation:
[0049] Weigh 3.91 g of Cu powder with a purity greater than 99.99%, 1.09 g of S powder, and 0.1 g of Fe3O4 magnetic powder, put the weighed powders into a ball mill, and mechanically alloy them under a protective atmosphere to obtain Cu 1.8 Sx% Fe3O4 precursor powder; the weight ratio of the spheres and the material during ball milling is 20-50:1, the rotation speed during ball milling is 300-600rpm, and the ball milling time is 1-4h. In this embodiment, the protective atmosphere is 5% H2+95% Ar, the mass ratio of the spheres and the material is 20:1, the ball milling speed is 425rpm, and the ball milling time is 2h.
[0050] Step (2) Cu 1.8 S-2%Fe3O4 bulk sintering:
[0051] The Cu prepared in step (1) is sintered by spark plasma sintering technology. 1.8 S-2% Fe3O4 precursor powder is sintered. First, the powder is poured into a graphite mold with a diameter of 15 mm and sintered at a temperature of 300-500°C and a pressure of 10-50 MPa for 5-30 min. In this embodiment, the sintering temperature is 500°C, the sintering pressure is 50 MPa, and the sintering time is 5 min to form a block of Cu 1.8 S-2%Fe3O4 porous magnetic copper sulfide thermoelectric material. 1.8 The main phase of S-2%Fe3O4 porous magnetic copper sulfide thermoelectric material is Cu 1.8 S.
[0052] The difference between Example 2-7 and Example 1 is that the parameters shown in Table 1 are different, that is, the content of the Fe3O4 second phase is different. The material formed in Example 2 is Cu 1.8 S-0.5% Fe3O4 porous magnetic copper sulfide thermoelectric material; the material formed in Example 3 is Cu 1.8 S-1% Fe3O4 porous magnetic copper sulfide thermoelectric material; the material formed in Example 4 is Cu 1.8 S-1.5% Fe3O4 porous magnetic copper sulfide thermoelectric material; the material formed in Example 5 is Cu 1.8S-2.5% Fe3O4 porous magnetic copper sulfide thermoelectric material; the material formed in Example 6 is Cu 1.8 S-3% Fe3O4 porous magnetic copper sulfide thermoelectric material; the material formed in Example 7 is Cu 1.8 S-20% Fe3O4 porous magnetic copper sulfide thermoelectric material. The difference between Comparative Example 1 and Example 1 is that the parameters shown in Table 1 are different, that is, the type of the second phase is different. The material formed in Comparative Example 1 is Cu 1.8 S-2%Fe magnetic copper sulfide thermoelectric material. The difference between Comparative Examples 3-5 and Example 1 is that the parameters shown in Table 1 are different, that is, the type and content of the second phase are different. The material formed in Comparative Example 3 is Cu 1.8 S-1% SiO2 copper sulfide thermoelectric material; the material formed in Comparative Example 4 is Cu 1.8 S-1% WO3 copper sulfide thermoelectric material; the material formed in Comparative Example 5 is Cu 1.8 S-1% SnO2 copper sulfide thermoelectric material.
[0053] Experimental Example 1 Morphology Characterization
[0054] The porous magnetic copper sulfide thermoelectric materials prepared in Examples 1-7 and Comparative Example 1 were observed using a scanning electron microscope. Taking Example 1 as an example, the obtained electron microscope images are as follows: Figure 1 The results show that a porous magnetic copper sulfide thermoelectric material is prepared by this method, wherein Figure 1 Cu 1.8 S-2wt%Fe3O4 thermoelectric material.
[0055] Experimental Example 2 XRD (X-ray Diffraction) Characterization
[0056] The porous magnetic copper sulfide thermoelectric materials prepared in Examples 1-7 and Comparative Example 1 and the thermoelectric material provided in Comparative Example 2 were tested by X-ray diffractometer. Taking Example 1 and Comparative Example 2 as examples, the test results are as follows: Figure 2 XRD results show that the mechanical alloying method and spark plasma sintering technology can be used to synthesize Cu 1.8 Porous magnetic copper sulfide bulk material with S as the main phase.
[0057] Experimental Example 3 Characterization of Thermoelectric Performance
[0058] The performance of thermoelectric materials is characterized by the dimensionless thermoelectric figure of merit ZT, which is expressed as ZT = S 2 σT / κ, where S 2 σ represents the power factor, T is the absolute temperature, and κ is the thermal conductivity.
[0059] 3.1 Electrical transmission performance
[0060] The thermoelectric materials prepared in Examples 1-7, Comparative Examples 1-5 and the thermoelectric material provided in Comparative Example 2 were cut into 3×3×10 mm cuboids and the resistivity and Seebeck coefficient test system was used to test the resistivity and Seebeck coefficient of the materials. Taking Example 1 and Comparative Example 2 as examples, the conductivity test results are as follows: Figure 3 As shown, the Seebeck coefficient test results are as follows Figure 4 The electrical conductivity and Seebeck coefficient of the thermoelectric materials provided in Examples 1-7 and Comparative Examples 1-5 at 773K are specifically shown in Table 2.
[0061] 3.2 Thermal conductivity
[0062] The bulk thermoelectric materials prepared in Examples 1-7 and Comparative Examples 1-5 were cut into The thermal conductivity of the circular sheet was tested by a laser thermal conductivity meter. Taking Example 1 and Comparative Example 2 as examples, the test results are as follows Figure 5 The thermal conductivity of the bulk thermoelectric composite materials prepared in Examples 1-7 and Comparative Examples 1-5 at 773K is specifically shown in Table 2.
[0063] 3.3ZT value
[0064] According to the above formula ZT=S 2 The ZT value can be obtained by calculating σT / κ. Taking Example 1 and Comparative Example 2 as examples, the ZT values are as follows: Figure 6 The ZT values of the bulk thermoelectric composite materials prepared in Examples 1-7 and Comparative Examples 1-5 at 773K are specifically shown in Table 2.
[0065] Table 2
[0066]
[0067] Experimental Example 4 Magnetic Characterization
[0068] The bulk thermoelectric material prepared in Example 1 and the thermoelectric material provided in Comparative Example 2 were cut and polished into rectangular blocks with a size of less than 2×2×2 mm for magnetic testing. Taking Example 1 and Comparative Example 2 as examples, the magnetic properties of the materials were measured using the hysteresis loop test. The hysteresis loops of the samples in Example 1 and Comparative Example 2 at 323 K are as follows: Figure 7 shown.
[0069] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A high-performance porous magnetic copper sulfide thermoelectric material, characterized in that: Including the matrix phase Cu 1.8 S and the second phase Fe3O4, whose general chemical formula is Cu 1.8 Sx%Fe3O4, where 0.5≤x≤20.
2. A high-performance porous magnetic copper sulfide thermoelectric material according to claim 1, characterized in that: Fe3O4 is a black oxide powder with magnetic properties, and the addition amount of Fe3O4 is 0.5 to 20 wt%.
3. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 1 or 2, characterized in that: The steps include: Step (1) Cu 1.8 Preparation of Sx% Fe3O4 precursor powder: Cu single substance powder, S single substance powder and Fe3O4 magnetic powder are placed in a ball mill for mechanical alloying to obtain Cu 1.8 Sx%Fe3O4 precursor powder; Step (2) Cu 1.8 Sintering of Sx%Fe3O4 bulk: Sinter the Cu prepared in step (1) 1.8 The Sx%Fe3O4 precursor powder is sintered by spark plasma sintering to obtain a porous magnetic copper sulfide thermoelectric material.
4. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 3, characterized in that: In step (1), the mechanical alloying process is carried out under a protective atmosphere.
5. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 4, characterized in that: The protective atmosphere is 5% H2+95% Ar.
6. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 5, characterized in that: In step (1), the purity of the Cu single substance powder and the S single substance powder are both greater than 99.99%.
7. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 6, characterized in that: In step (1), the weight ratio of the ball to the material during ball milling is 20-50:1, the rotation speed during ball milling is 300-600 rpm, and the ball milling time is 1-4 hours.
8. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 7, characterized in that: In step (2), the sintering temperature is 300-500° C., the sintering time is 5-30 min, and the sintering pressure is 10-50 MPa.
9. The method for preparing a high-performance porous magnetic copper sulfide thermoelectric material according to claim 8, characterized in that: In step (2), the sintering temperature is 500° C., the sintering time is 5 min, and the sintering pressure is 50 MPa.
Citation Information
Patent Citations
Preparation method of Cu1.8+xS binary thermoelectric material
CN102363530A
Amorphous nano copper sulphide magnetic composite material, as well as preparation method and application thereof
CN104492369A
Enzyme response type magnetic nano particles and preparation method and application thereof
CN105031651A
Preparation method of copper sulfide-based plastic thermoelectric composite material
CN118660610A
